The Impact from the Implementation of Online Single Submission (OSS) towards the Ease of Business Licensing for Business Actors in North Sumatera Province - Tobing, Rinto Mujiono Lumban; Bengkel, Bengkel; Irmayani, Tengku (Dinasti Publisher, 2023)
This study aims to explore and analyze futher the impact from implementing online single submission (OSS) on the ease of business licensing for business actors in North Sumatera Province. Quantitative method chosen as the research method. The research population are those business actors or permit applicants who have been served by the Investment Service and One-Stop Integrated Licensing Services of North Sumatera Province in obtaining permits on average as many as 180 permit applicants per month, according to permit data management during period of 2021 there are total sample of 108 respondents who divided into large-scale business actors, medium-scale business actors and small-scale business actors. The findings of this research indicates: 1) The Implementation of OSS in North Sumatera Province has been running well and effective 2) Based on the analysis separately, there are two variables which have positive and significant impact to the ease of business licensing, namely communication and bureaucratic structure; 3) The implementation of OSS in North Sumatera Province is good deal, because it has proven to have an impact towards the ease of business licensing in North Sumatera as shown by the policy implementation model of George C. Edward III which reached 65.8 percent.